2017
DOI: 10.1093/mnras/stx1835
|View full text |Cite
|
Sign up to set email alerts
|

Integral-field kinematics and stellar populations of early-type galaxies out to three half-light radii

Abstract: We observed twelve nearby H i-detected early-type galaxies (ETGs) of stellar mass ∼ 10 10 M M * ∼ 10 11 M with the Mitchell Integral-Field Spectrograph, reaching approximately three half-light radii in most cases. We extracted line-of-sight velocity distributions for the stellar and gaseous components. We find little evidence of transitions in the stellar kinematics of the galaxies in our sample beyond the central effective radius, with centrally fast-rotating galaxies remaining fast-rotating and centrally slo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
29
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 79 publications
3
29
0
Order By: Relevance
“…However, this trend disappears at larger radii (∼1-1.5 Re), suggesting a complex contribution of stellar populations in the outer regions, as they are formed ex-situ from a range of merging satellites. Boardman et al (2017) found that the kinematics in a sample of 12 ETGs, detected in HI, did not show any variations out to three effective radii, supporting the idea that these galaxies have not undergone dry major merging at late times. However, the IFU data revealed substantial population gradients consistent with some level of interaction in recent times.…”
Section: Introductionmentioning
confidence: 80%
“…However, this trend disappears at larger radii (∼1-1.5 Re), suggesting a complex contribution of stellar populations in the outer regions, as they are formed ex-situ from a range of merging satellites. Boardman et al (2017) found that the kinematics in a sample of 12 ETGs, detected in HI, did not show any variations out to three effective radii, supporting the idea that these galaxies have not undergone dry major merging at late times. However, the IFU data revealed substantial population gradients consistent with some level of interaction in recent times.…”
Section: Introductionmentioning
confidence: 80%
“…Using the SAURON spectrograph, Weijmans et al (2009) confirmed the decreasing rotational support of the lenticular galaxy (S0) NGC 821 at large radii. However, Raskutti et al (2014) and Boardman et al (2017) did not find significant kinematic transitions in a sample of galaxies observed with the Mitchell Spectrograph. This discrepancy was attributed to differences in the sample selection of the respective studies.…”
mentioning
confidence: 75%
“…Emsellem et al 2007;Cappellari et al 2011) and been unable to probe this transition. Notable progress has been achieved using the wide-field Mitchell Spectrograph (Raskutti et al 2014;Boardman et al 2017) and the use of wide-field multiple slit spectrographs as "proxy" IFUs (e.g. Proctor et al 2009;Arnold et al 2011).…”
mentioning
confidence: 99%
“…The 2D gas kinematics is disc dominated by disc rotation, classified as a near-oblate, face-on fast rotator by Boardman et al (2016). Some anisotropies and signs of warps are found at large galactocentric distance likely related to a past interaction (Boardman et al 2017). The disc kinematics is not fully captured by our ground-based spectroscopy likely due to the slit orientation with respect to the major axis (Fig.…”
Section: Appendix B: Comments Spectra and Images Of Individual Sourcesmentioning
confidence: 92%